THE IMPROVEMENT OF ACCOUNTING AND DOCUMENTATION OF THE GOODS SALE THROUGH ELECTRONIC SETTLEMENT METHODS - Eudochia BAJEREAN; Andrei JIZDAN (Eastern European Journal of Regional Studies, 2023)
The domestic commercial entities use as an alternative settlement method: payment services offered by e-money companies. This article is intended for both theoreticians and practising accountants, since, in addition to developing the existing theoretical basis, the aim is to identify relevant solutions for solving problematic accounting issues related to the documentation of the use of local payment services. Technological progress does not stand still, and in the last decade, so-called companies issuing electronic money have started to appear on the local trade market of the Republic of Moldova. The importance of the topic requires research into the practical application and accounting of transactions related to the use of payment services offered by e-money companies. The applied research methodology involves both general and specific approaches such as: analytical method, web-graphical analysis, synthesis method, comparison method, systemic method and other relevant research methods. Therefore, in the following, an attempt will be made to identify the correct way of documenting the cash collection process by applying domestic payment services.